Flexible hoses, end fittings and sockets for gas burning appliances. Strip-wound metallic flexible hoses, covers, end fittings and sockets for domestic appliances burning 1st, 2nd and 3rd family gases. Specification Part 1, (28th January 2022) - British Standards Institution,
No abstract available